1960
DOI: 10.1002/cber.19600930132
|View full text |Cite
|
Sign up to set email alerts
|

Strukturbestimmungen von ungesättigten Ketonen mit Hilfe von Infrarot‐ und Ultraviolett‐Spektren

Abstract: Absolute Intensitatsmessungen im IRund UV-Spektrum (VC=O-, VC=C-und K-Banden) bringen den Beweis, daB --entgegen der Ansicht BRAUDESkonjugiert ungeslttigte Ketone s-cis-Konstellation besitzen, wenn die ebene s-trans-Form wegcn sterischer Hinderung unmoglich ist.nungen entsprechen einander).Gruppe A + B: Gesattigte undunkonjugiertungesattigteKetone, Nr.1-16 ( 0 0 . 0 ) *):DiePunkteliegenengurnden Mittelwert vcz0 = 1719crn-1 und I = 5.40 crn3/Mol**). 6) A. BURAWOY, Ber. dtsch. chem. Ges. 63, 3155 [1930]; L. K. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1961
1961
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Siiiiilar effects in tlie ultraviolet spectra of conjugated carbonyl compounds and certain differences in the infrared and Raman spectra of coinpounds of kno\vn geometry (7)(8)(9)(10)(11)(12) have been suggested to distinguish between tlie two planar cornforiiiations. Tlie general characteristics of the two forms are sumiilarized iii Table VIII.…”
Section: Steric I~zlzibition Of Conjugationmentioning
confidence: 99%
“…Siiiiilar effects in tlie ultraviolet spectra of conjugated carbonyl compounds and certain differences in the infrared and Raman spectra of coinpounds of kno\vn geometry (7)(8)(9)(10)(11)(12) have been suggested to distinguish between tlie two planar cornforiiiations. Tlie general characteristics of the two forms are sumiilarized iii Table VIII.…”
Section: Steric I~zlzibition Of Conjugationmentioning
confidence: 99%
“…We assume that the rotation defined by  3 is too strongly hindered, 27 and optimize the geometry with no constraints on this dihedral angle.…”
Section: Ab Initio Calculationsmentioning
confidence: 99%
“…The preparation and purification of the ketones have been described by IIIeclte and Koacli (2). The infrared spectra were measured on Perkin-Elmer A/Iodel 21 and NIodel 112 spectronleters using the low-temperature technique described previously (6).…”
Section: Esperiaienti-\l Meti-iods a N D R E S U L T Smentioning
confidence: 99%
“…The s-cis (I) and s-trans (11) conformations of open-chain a,p-unsaturated ketones can be distinguished from the positions and intensities of the C=O and C=C stretching bands in the infrared (1)(2)(3)(4) and Ranla11 (5) spectra. In the liquid state most conjugated ketones exist predorni~la~ltly or perhaps exclusively in one or other of the two conformations, but NIecke and Noacli (2) have observed that the infrared spectrum of tratzs-A3-penten-2-one (IIIa) and related colnpoullds (IIIb-IIId) exhibit two carbony1 bands near 1700 cm-I and 1680 cm-I in tetracl~loroetl~yle~~e solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation